Quality assessment of meal protein and oil of thirty four promising genotypes of mustard [Brassica juncea (L.) Czern and Coss.]: QUALITY ASSESSMENT OF MEAL PROTEIN AND OIL OF PROMISING GENOTYPES OF MUSTARD - DURGESHWARI P GADPAYALE; ALKA KATIYAR; LALLU SINGH (Journal of Oilseeds Research, 2021)
Rapeseed mustard is an important source of edible oil in Indian diet especially in Eastern and North-Western India. The present investigation was carried out to assess some seed quality traits in thirty four genotypes/varieties of Indian mustard [Brassica juncea (L.) Czern&Coss] grown in U.P. We analyzed traits such as moisture content, protein content, test weight, polyphenol content, oil content, glucosinolate and nutritional quality index. The overall range of variability ofmoisture content, test weight, contents of oil, protein, polyphenol and nutritional quality index were 2.45-6.89%, 2.80-5.8g, 33.52-42.15%, 19.53-27.27%, 7.24-30.86 mg/100g, 7.56-12.78, respectively.